1996
DOI: 10.1016/s1074-7613(00)80483-5
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that a Single Peptide–MHC Complex on a Target Cell Can Elicit a Cytolytic T Cell Response

Abstract: Using a chemically homogeneous radiolabeled peptide of high specific activity (125I-QLSPYPFDL, 3.5 x 10(18) cpm per mole) we show that at a peptide concentration (5 pM) causing half-maximal lysis of target cells by a cytolytic T lymphocyte (CTL) clone that recognizes the peptide in association with Ld, a class I MHC protein, only 3 peptide molecules on average are bound by Ld per target cell. From the distribution of Ld on the target cells, we suggest that a single peptide-MHC complex per target cell can trigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
452
1
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 627 publications
(488 citation statements)
references
References 37 publications
28
452
1
1
Order By: Relevance
“…The number of peptide-HLA complexes required for a T lymphocyte response is not definitively known (38,39). Direct visualization of CTL epitope presentation on tumor cells and its relationship to CTL-mediated tumor cell lysis was a major finding of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The number of peptide-HLA complexes required for a T lymphocyte response is not definitively known (38,39). Direct visualization of CTL epitope presentation on tumor cells and its relationship to CTL-mediated tumor cell lysis was a major finding of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have generally shown that the number of peptide-MHC complexes per target cell required for recognition and cytolysis by differentiated CTL varies from several thousand to Ͻ10 (26 -30). Sykulev et al previously provided more indirect evidence that in target cells pulsed with an average of three peptide epitope molecules per cell, cells expressing a single peptide-MHC complex could be recognized by CTL (31). Consistent with our quantitation is the observation that unmanipulated HLA-B27 ϩ B-LCL are poorly recognized by RRIY-DLIEL-specific CTL, even though these effectors are of extremely high avidity (SD 50 ϭ 1-5 pM) based on peptide dose-response curves (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Their existence suggests a broader functional TCR repertoire via an expanded pool of potential antigenic epitopes. Although cryptic epitopes may be present in small abundance relative to traditional epitopes, the extreme sensitivity of CTL may compensate to allow efficient TCR detection and triggering of effector function (6).…”
mentioning
confidence: 99%